GLOBALIZATION CHALLENGES TO MODERN UNIVERSITY EDUCATION - Богдан Буяк (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
This article presents the analysis of one of the challenges to modern civilization, in particular, the one to its ability to resist destructive tendencies and support the creative and progressive ones in the context of the development of the educational sphere. The impact of the globalization processes on the system of university education in general, and the national university system in particular has been researched. The level of development of a university as an innovative higher educational institution has been made an assessment of. On the basis of the analysis of the achievements of prominent scientists on this issue a list of unsolved questions has been made, as well as the role of the given research in the solution of the mentioned problem was defined.